Chapter Twelve Revealing the Hidden Affliction How Much Infertility Was Due to Venereal Disease in England and Wales on the Eve of the Great War? - Szreter, Simon (University of Rochester Press, 2019)
By the turn of the twentieth century the British nation's declining birthrate was increasingly the subject of anxious public and scientific debate, as the Registrar General's annual reports continued to confirm a downward national trend, which had in fact commenced from the late 1870s.